The Effect of Regional Financial Management on Financial Distress of Local Government in Indonesia - Nashrullah, Moh. Haidar; Khomsiyah, Khomsiyah (Jurnal Indonesia Sosial Sains, 2024)
Deficits experienced by local governments can lead to financial difficulty, often referred to as financial distress. Although local governments experience deficits, local governments can avoid these conditions with good regional financial management. This research aims to determine regional financial management's effect on local governments' financial distress in 2019-2022. The sample in this research uses a total sampling technique at all provincial and local government levels in 2019-2022. This research uses secondary data with documentation techniques. Binary logistic regression was obtained to perform data analysis. The results showed that financial independence significantly negatively affects financial distress. Financial flexibility has a significant negative effect on financial distress. Operational solvency does not have a significant adverse effect on financial distress. Short-term solvency has a significant positive effect on finances. Service solvency has a significant negative effect.